2017
DOI: 10.1016/j.juro.2016.07.088
|View full text |Cite
|
Sign up to set email alerts
|

Linkage of Lower Urinary Tract Symptoms to Sleep Quality in Elderly Men with Nocturia: A Community Based Study Using Home Measured Electroencephalogram Data

Abstract: In elderly men with nocturia, sleep quality is associated with lower urinary tract function. Higher subjective sleep quality is associated with longer slow wave sleep time and less severe lower urinary tract symptoms. Higher objective sleep quality is further associated with a higher urinary flow rate and lower nocturnal urinary volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 17 publications
2
18
0
Order By: Relevance
“…Deep sleep, or restorative SWS, predominates in the first 3‐to‐4 hours of sleep . Disruption of deep sleep, for instance by nocturia, is likely to have a greater negative impact on sleep quality and general well‐being than waking up during rapid eye movement or light sleep . In our study, OAB treatment increased FUST, suggesting that participants were more likely to wake up during light sleep than deep sleep, which might subsequently lead to better overall health and quality of life.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Deep sleep, or restorative SWS, predominates in the first 3‐to‐4 hours of sleep . Disruption of deep sleep, for instance by nocturia, is likely to have a greater negative impact on sleep quality and general well‐being than waking up during rapid eye movement or light sleep . In our study, OAB treatment increased FUST, suggesting that participants were more likely to wake up during light sleep than deep sleep, which might subsequently lead to better overall health and quality of life.…”
Section: Discussionmentioning
confidence: 58%
“…Previous studies have consistently demonstrated a close relationship between nocturia and sleep . Interrupted sleep due to nocturia has been linked to fatigue, decreased concentration, lower performance at work and increased risk of accidents .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is difficult for nocturia patients who go to the toilet for voiding to undergo polysomnography, which fixes patients to the bed during the sleep period. The portable EEG device used in this study does not restrain patients and was demonstrated as useful in our previous study, which demonstrated the linkage between sleep quality assessed by the PSQI and slow-wave sleep time [14].…”
Section: Discussionmentioning
confidence: 96%
“…5 Restless sleep, long latency before falling and returning to sleep, and shorter total duration of sleep all correlate with high bother in men with nocturia. 5,6 Furthermore, the link between poor sleep and depression has been well described. 7 Successful treatment of nocturnal polyuria, the most prevalent underlying cause of nocturia, has been shown to increase time slept before an individual's first nocturia episode (first undisturbed sleep time or FUST).…”
mentioning
confidence: 99%